Cartographie Des Risques De L’erosion Hydrique Par L’equation Universelle Revisee Des Pertes En Sols, La Teledetection Et Les Sig Dans Le Bassin Versant De L’ourika (Haut Atlas, Maroc) - Modeste, Meliho; Abdellatif, Khattabi; Nadia, Mhammdi; Zhang, Hongming (European Scientific Journal, ESJ, 2016)
Covering an area of 576 square kilometers, the Ourika watershed is a sub-watershed of the large Tensift basin, located on the northwest slopes of the Marrakech High Atlas, in mid-west Morocco. This basin of dramatic topography, with sparse vegetation cover and friable substrates, is under increasing human action exacerbated by a variable and changing climate. Its vulnerability to water erosion is quite high, increasing risks of wadi flows with significant sediment loads. The aim of this work was to quantify soil loss in the basin using the Revised Universal Soil Loss Equation (RUSLE) and Geographic Information System. The results showed that the Ourika watershed was subject to strong climatic aggressiveness ranging from 55.22 to 100.57 MJ.mm/ha.h. The average soil erodibility value, K, was 0.48 t.ha.h/ha.MJ.mm, with a standard deviation of 0.28 t.ha.h/ha.MJ.mm. Slopes with values higher than 35% represented 72% of the watershed’s area, with the topographic factor, LS, values ranging from 0.01 to 94.5. The vegetation factor was high throughout the Ourika watershed while C values were higher than 0.5 for 73% of the watershed’s area. The average soil loss obtained in the basin was 380 t/ha/year. These results indicated that 48% of the watershed’s area was subject to a soil loss between 50-400 t/ha/year, and between 400 and 1000 t/ha/year for 30% of the watershed. Soil loss below the tolerance level (<7 t/ha/year) represented only 4% of the watershed area. These findings served in highlighting the significance of erosion in the Ourika watershed.